2013
DOI: 10.1080/17470218.2012.721379
|View full text |Cite
|
Sign up to set email alerts
|

Prospective memory and ageing paradox with event-based tasks: A study of young, young-old, and old-old participants

Abstract: Research on ageing and prospective memory—remembering to do something in the future—has resulted in paradoxical findings, whereby older adults are often impaired in the laboratory but perform significantly better than younger adults in naturalistic settings. Nevertheless, there are very few studies that have examined prospective memory both in and outside the laboratory using the same sample of young and old participants. Moreover, most naturalistic studies have used time-based tasks, and it is unclear whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
48
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 31 publications
2
48
0
2
Order By: Relevance
“…But importantly, for the two event-based tasks in laboratory settings the authors note that they could not be certain that the intention had left consciousness before the introduction of the cue circa 10 minutes later. Kvavilashvili et al (2013) therefore suggest that the inconsistent pattern within eventbased PM is due to differences in ongoing task demands between studies measuring PM in lab and in natural settings, and across studies.…”
Section: Chapter 2 Prospective Memory and Cognitive Agingmentioning
confidence: 99%
See 4 more Smart Citations
“…But importantly, for the two event-based tasks in laboratory settings the authors note that they could not be certain that the intention had left consciousness before the introduction of the cue circa 10 minutes later. Kvavilashvili et al (2013) therefore suggest that the inconsistent pattern within eventbased PM is due to differences in ongoing task demands between studies measuring PM in lab and in natural settings, and across studies.…”
Section: Chapter 2 Prospective Memory and Cognitive Agingmentioning
confidence: 99%
“…A recent study by Kvavilashvili et al (2013) compared the age groups 18-30, 61-70, 71-80, for which they found no in-between significant differences for the prospective or the retrospective components in natural settings. When comparing between measures of processing speed, retrospective memory and two traditional laboratory-based PM event-based tasks within the same sample, they found significant age-related declines.…”
Section: Chapter 2 Prospective Memory and Cognitive Agingmentioning
confidence: 99%
See 3 more Smart Citations